Characterizing forest vulnerability and risk to climate‐change hazards. Issue 2 (28th October 2020) - Lecina‐Diaz, Judit; Martínez‐Vilalta, Jordi; Alvarez, Albert; Banqué, Mireia; Birkmann, Jörn; Feldmeyer, Daniel; Vayreda, Jordi; Retana, Javier
Abstract : Wildfires, drought, insect outbreaks, and windstorms are altering the forest‐associated ecosystem services that are essential for human well‐being, and the impacts of such events are likely to increase under ongoing climate change. However, a widely accepted and operational framework for evaluating forest vulnerability and risk to these disturbances remains lacking. We propose a general framework to assess forest vulnerability and risk based on the widely used concepts of exposure, hazard magnitude, susceptibility, and lack of adaptive capacity as defined by the Intergovernmental Panel on Climate Change. We suggest a standardized procedure for defining and combining these components, as well as a list of indicators readily applicable to the primary hazards to forests associated with climate change. This framework and its methodology constitute a basis for a systematic assessment of forest risk and vulnerability for policy makers, as well as for forest and land managers, that can aid in the development of forward‐looking policies.